The challenges of the relationship between university and business - Ratangar, Djimnadjingar; Abakar, Senoussi Seid; Saleh, Moussa Kabir (Edelweiss Applied Science and Technology, 2024)
The academic and business worlds have often been seen as two very different worlds, one focusing on scientific research the other confined to practical production activities. In this article, we will attempt to explore the mechanisms the mechanisms that can bring the product of university higher education with the demand for human resources by companies, through the through the creation of a university-enterprise interface to encourage the worlds of academia and business to meet, work better together.